Synthesis of Polycyclic Imidazoles via α-C–H/N–H Annulation of Alicyclic Amines - Dutta, Subhradeep; Bhatt, Kamal; Cuffel, Fabian; Seidel, Daniel (Synthesis, 2023)
Secondary alicyclic amines are converted into their corresponding ring-fused imidazoles in a simple procedure consisting of oxidative imine formation followed by a van Leusen reaction. Amines with an existing α-substituent undergo regioselective ring-fusion at the α′-position. This method was utilized in a synthesis of fadrozole.
Keywords: C–H bond functionalization; amines; annulation; imidazoles; heterocycles